ChemInform Abstract: A Trigonal‐Prismatic Hexanuclear Technetium(II) Bromide Cluster: Solid‐State Synthesis and Crystallographic and Electronic Structure. Issue 29 (1st July 2013) - Johnstone, Erik V.; Grant, Daniel J.; Poineau, Frederic; Fox, Laura; Forster, Paul M.; Ma, Longzou; Gagliardi, Laura; Czerwinski, Kenneth R.; Sattelberger, Alfred P.
Abstract: Na[Tc6 Br12 ]2 Br is obtained by thermal decomposition of TcBr4 (Na source not given; evacuated Pyrex ampule, 1.